If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x(9x + 4) = 0 Reorder the terms: 7x(4 + 9x) = 0 (4 * 7x + 9x * 7x) = 0 (28x + 63x2) = 0 Solving 28x + 63x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '7x'. 7x(4 + 9x) = 0 Ignore the factor 7.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(4 + 9x)' equal to zero and attempt to solve: Simplifying 4 + 9x = 0 Solving 4 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 9x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 9x = 0 + -4 9x = 0 + -4 Combine like terms: 0 + -4 = -4 9x = -4 Divide each side by '9'. x = -0.4444444444 Simplifying x = -0.4444444444Solution
x = {0, -0.4444444444}
| 2r-6+5r=3r+7 | | 2x/3-=x/6-5/2 | | 7x+4x+27=180 | | X^2+8x+16=1.77777778 | | 10(4+q)=76 | | 0=0.4*(6x-3*((1-x)-2)) | | -57.5=-4.6x | | 5+47(21+3x)=41 | | x^2-xy+3x+2=0 | | 15=45/x | | Y+4.3=.1x | | 5c+3d-3c+2d-4= | | 36.6=-12.2n | | -2(y-4y)+7=-3(4y-y)+4+14y | | 6d/-2=5 | | 6z=41/2z-8 | | (3x-9)(x+5)= | | 4.2n=65.1 | | 4*7n=182 | | 7t-13-2t=9t+5t | | 4k=3(2+k) | | x/1.2=1.5 | | x-(4/5)=4(1/3) | | 5(x+6)+8=7x-8 | | 4.2n=65d | | 0=0.5*(6x-3*((1-x)-2)) | | x^2/-4000 | | 4x^2/10x=y | | 0.6x=-0.36 | | (-3x+54)+(11x+4)=90 | | g=6*x | | 1/3x63 |